Inventory and Assessment of Flowering Plants in the Sanobharyang Area of Kathmandu, Nepal - Chataut, Gajendra Prasad; Paudel, Basudev; Sharma, Krishna Prasad (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
Documentation of flowering plants was carried out in the Sanobharyang area of Kathmandu, Nepal by direct observation method. Altogether 158 species of flowering plants with 138 genera and 60 families were recorded. Among these families Asteraceae had the highest number of species while 29 families had only one species each. Out of the total, 84 (52%) species were native and 74 (48%) species were non native including 10 (6%) invasive alien plant species. This study shows that a significant number of flowering plants can be conserved by maintaining the open spaces in the public places, roadsides and home gardens even in the densely populated part of the city.